Listeners’ Interpretation of the Meanings of the Lyrics of “Nina,” “O, Tuan,” and “Tarot” by Feast: A Reception Study Based on Wolfgang Iser’s Theory - Vanessa Salsabila Anjani; Ririn Nurul Azizah (The Future of Education Journal, 2026)
This study aims to analyze listeners’ interpretations of the songs Nina, O, Tuan, and Tarot by Feast based on Wolfgang Iser’s reception theory. This research employs a qualitative approach with a descriptive-reception design. The data consist of listeners’ comments on YouTube containing interpretations and emotional responses. Data collection was conducted through textual observation of song lyrics and digital document analysis using purposive sampling. Data were analyzed thematically through data reduction, categorization, interpretation, and conclusion drawing, guided by the concepts of gaps and aesthetic response. Data validity was ensured through source and technique triangulation. The findings show that the meaning of song lyrics is dynamic and not fixed but constructed through interaction between text and listeners via a gap-filling process. Nina is interpreted as reflecting family relationships and motivation, O, Tuan as experiences of loss and emotional awareness, and Tarot as representations of uncertainty and existential search. These interpretations are influenced by listeners’ social backgrounds, experiences, and emotional conditions. This study confirms that song meaning is open and constructed according to the listeners’ horizon of experience in digital culture.